Rotator cuff tear: A detailed update - Vivek Pandey; W. Jaap Willems (Elsevier, 2015)
Rotator cuff tear has been a known entity for orthopaedic surgeons for more than two hundred years. Although the exact pathogenesis is controversial, a combination of intrinsic factors proposed by Codman and extrinsic factors theorized by Neer is likely responsible for most rotator cuff tears. Magnetic resonance imaging remains the gold standard for the diagnosis of rotator cuff tears, but the emergence of ultrasound has revolutionized the diagnostic capability. Even though mini-open rotator cuff repair is still commonly performed, and results are comparable to arthroscopic repair, all-arthroscopic repair of rotator cuff tear is now fast becoming a standard care for rotator cuff repair. Appropriate knowledge of pathology and healing pattern of cuff, strong and biological repair techniques, better suture anchors, and gradual rehabilitation of postcuff repair have led to good to excellent outcome after repair. As the healing of degenerative cuff tear remains unpredictable, the role of biological agents such as platelet-rich plasma and stem cells for postcuff repair augmentation is still under evaluation. The role of scaffolds in massive cuff tear is also being probed.